Perlindungan Hukum Kawasan Hutan Adat dan Hak Ulayat - Obed Edotalino Sudiro; Slamet Suhartono (Lembaga Pengembangan Kinerja Dosen, 2024)
The increasingly rapid development of the times has opened people's views to be more open to various kinds of world and national problems. Technology, which is one of the tools for thinking, has created innovative patterns of thinking in society that are mature in determining diverse perspectives and actions, as well as every outcome of views and attitudes that is permitted as long as it does not violate the rules and norms that have been regulated in state life. Customary forests are one of the categories of social forestry which are located in the living areas of local indigenous communities and can usually be found in inland areas. Customary forests are also regulated in Law Number 41 of 1999 concerning Forestry as stated in Article 1 number 6